2017
DOI: 10.1007/s00289-017-2163-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of highly filled epoxy composites modified with walnut shell waste filler

Abstract: Epoxy composites modified with ground walnut shell used as organic waste fillers were prepared and examined. Post-agricultural waste materials after grinding were characterized by evaluation of grain size distribution and structure observations realized using scanning electron microscope (SEM). The influence of filler addition on the mechanical properties of epoxy-based composites was determined by: static tensile test, Charpy impact test, and ball indentation hardness measurements. Composite samples containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 39 publications
9
62
0
Order By: Relevance
“…[60] It was observed that microhardness increased with the addition of TPS particles into the matrix. A similar observation was also made by previous researchers in case of tamarind seed, [18] walnut shell, [61] rice husk, [62] coconut shell, [16,63] and hazelnut shell [64] particles. The lowest value of hardness of the matrix before reinforcement was 21.04 HV.…”
Section: Density and Void Contentsupporting
confidence: 89%
“…[60] It was observed that microhardness increased with the addition of TPS particles into the matrix. A similar observation was also made by previous researchers in case of tamarind seed, [18] walnut shell, [61] rice husk, [62] coconut shell, [16,63] and hazelnut shell [64] particles. The lowest value of hardness of the matrix before reinforcement was 21.04 HV.…”
Section: Density and Void Contentsupporting
confidence: 89%
“…Research institutions and industry undertake efforts to make chemical production more eco-friendly and to replace fossil raw materials with renewable feedstock [1]. More and more research concerns modification of polymers with waste [2][3][4][5][6]. Among the renewable raw materials, vegetable oils are the most widely used in the synthesis of different chemicals, which could be applied by the polymer industry [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is much more pronounced at high temperatures when the chain motion or vibration is greater [22,61]. Comparing the composites according to the type of reinforcement, it can be seen that the reinforced composites with coarse particles (CFF) have a higher modulus at high temperatures, thus showing their higher capacity to maintain the mechanical load with recoverable viscoelastic deformation at high temperatures compared to the FFF-reinforced composites [56]. Figure 6b shows the dynamic damping factor (tan δ) evolution regarding temperature.…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…Therefore, it is evident that with the The grinding process has a relevant effect on both particle aggregate and geometry. Despite this, these differences can be seen in Figure 2 since in general, both CFF and FFF particles had an irregular morphology with a rough surface and the presence of granular fractures (typical morphology of hard lignocellulosic particles after being subjected to crushing processes [54][55][56]). Figure 3 shows in a more detailed way the above-mentioned effects.…”
Section: Morphology Of Ff Particlesmentioning
confidence: 99%
See 1 more Smart Citation